Équations équilibrées la veille |
8 KMnO4 + 7 H2SO4 + 5 H2S = 4 K2SO4 + 8 MnSO4 + 12 H2O
F2 + C = F2C =>
F2 + C = F2C
KBrO3 + H2S = KBr + H2O + S =>
KBrO3 + 3 H2S = KBr + 3 H2O + 3 S
Os(OH)8 + HF = OsF8 + H2O =>
Os(OH)8 + 8 HF = OsF8 + 8 H2O
Mg(OH)(s) + HCl(aq) = H2O(l) + MgCl(aq) =>
Mg(OH)(s) + HCl(aq) = H2O(l) + MgCl(aq)
Pb3N4 + KI = PbI4 + K3N =>
Pb3N4 + 12 KI = 3 PbI4 + 4 K3N
Fe + H2SO4 = Fe2(SO4)3 + H2 =>
2 Fe + 3 H2SO4 = Fe2(SO4)3 + 3 H2
NaMnO4 + NaBr + H2O = Mn02 + NaBrO3 + NaOH =>
6 NaMnO4 + 7 NaBr + 3 H2O = 3 Mn02 + 7 NaBrO3 + 6 NaOH
CuCl2 + K2(CrO4) = Cu(CrO4) + K + Cl =>
CuCl2 + K2(CrO4) = Cu(CrO4) + 2 K + 2 Cl
Ir(CO3)2 + MoBr3 = Mo2(CO3)3 + IrBr4 =>
3 Ir(CO3)2 + 4 MoBr3 = 2 Mo2(CO3)3 + 3 IrBr4
NaOH + ZnO = NaO + ZnOH =>
NaOH + ZnO = NaO + ZnOH
K2CO3(aq) + SnCl4(aq) = K2Sn + CO3Cl4 =>
K2CO3(aq) + SnCl4(aq) = K2Sn + CO3Cl4
Mn + HBr = MnBr4 + H2 =>
Mn + 4 HBr = MnBr4 + 2 H2
Fe3C + PbO2 + HNO3 = Pb(NO3)2 + Fe(NO3)3 + CO2 + H2O =>
2 Fe3C + 13 PbO2 + 44 HNO3 = 13 Pb(NO3)2 + 6 Fe(NO3)3 + 2 CO2 + 22 H2O
KMnO4 + NH3 = KNO4 + MnO2 + KOH + H2O =>
10 KMnO4 + 3 NH3 = 3 KNO4 + 10 MnO2 + 7 KOH + H2O
NaHCO3(s) + HClO4(aq) = CO2(g) + H2O(l) + NaClO4(s) =>
NaHCO3(s) + HClO4(aq) = CO2(g) + H2O(l) + NaClO4(s)
FeCl2(aq) + Li3PO4 = LiCl(aq) + Fe3(PO4)2(aq) =>
3 FeCl2(aq) + 2 Li3PO4 = 6 LiCl(aq) + Fe3(PO4)2(aq)
O2 + Ag + V2O5 = AgVO3 =>
O2 + 4 Ag + 2 V2O5 = 4 AgVO3
Al(s) + HBr(aq) = AlBr3(aq) + H2(g) =>
2 Al(s) + 6 HBr(aq) = 2 AlBr3(aq) + 3 H2(g)
Na + H2O = NaOH + H2 =>
2 Na + 2 H2O = 2 NaOH + H2
Pb(SO4)2 + H2O = H2(SO4)2 + PbO =>
Pb(SO4)2 + H2O = H2(SO4)2 + PbO
MnO4{-} + As2O3 + H2O = Mn2O3 + AsO4{-3} + H{+} =>
2 MnO4{-} + 2 As2O3 + 5 H2O = Mn2O3 + 4 AsO4{-3} + 10 H{+}
F2 + C = F2C =>
F2 + C = F2C
Al2(SO3)3 + Ca(CIO3)2 = Al(CIO3)3 + CaSO3 =>
Al2(SO3)3 + 3 Ca(CIO3)2 = 2 Al(CIO3)3 + 3 CaSO3
PhCH2NH2 + HCl = PhCH2Cl + NH3 =>
PhCH2NH2 + HCl = PhCH2Cl + NH3
CF4 + Br2 = CBr4 + F2 =>
CF4 + 2 Br2 = CBr4 + 2 F2
KBr + HCl = KCl + HBr =>
KBr + HCl = KCl + HBr
NaOH + H2CO3 = Na2CO3 + H2O =>
2 NaOH + H2CO3 = Na2CO3 + 2 H2O
F2 + C = F2C =>
F2 + C = F2C